2014
DOI: 10.5812/ircmj.16086
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol, Ondansetron, Granisetron, Magnesium Sulfate and Lidocaine and Reduced Propofol Injection Pain

Abstract: Background:Propofol is a most widely used intravenous anesthetic drug. One of its most common complications is the pain upon injection; therefore, different methods, with various effects, have been proposed in order to alleviate the pain.Objectives:This study investigates the effects of paracetamol, ondansetron, granisetron, magnesium sulfate and lidocaine drugs on reducing the pain of propofol injection during anesthetic induction. Also, the hemodynamic changes will be analyzed.Patients and Methods:This is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
4
33
2
Order By: Relevance
“…The effects of lidocaine and granisetron are similar (69.64%) and higher than the other groups. The effects of magnesium sulfate (51.78%), ondansetron (39.28%) and paracetamol (28.57%) are less than the lidocaine and granisetron, therefore, these results were not matched with our results [30].…”
contrasting
confidence: 57%
“…The effects of lidocaine and granisetron are similar (69.64%) and higher than the other groups. The effects of magnesium sulfate (51.78%), ondansetron (39.28%) and paracetamol (28.57%) are less than the lidocaine and granisetron, therefore, these results were not matched with our results [30].…”
contrasting
confidence: 57%
“…They got significant decrease in pain with 20mg lidocaine on propofol injection is much less than the lidocaine dose that we used, and this discrepancy may be because they mixed propofol with lidocaine and their research done only on female gender [19]. Ali pour M et al, studied 336 patients compared many drugs and lidocaine to placebo on reducing the pain of propofol injection, the result showed that lidocaine is more significantly reduces pain on propofol injection than the other groups [ 20]. MGupto, S Mishro et al, studied a 100 female patients for evaluation lidocaine, pethidine, dexamethasone compared to placebo group results to decrease the incidence of propofol pain showed that all pretreatment groups the incidence of propofol injection pain reduces considerably more than placebo [9].…”
Section: Discussionmentioning
confidence: 82%
“…In another study, titled "Paracetamol, Ondansetron, Granisetron, Magnesium Sulfate and Lidocaine and Reduced Propofol injection pain" by Alipour et al 18 showed pain observed with Paracetamol in 72% patients, Ondansetron61%, granesetron30% Magnesium 48% and Lidocaine 30% patients.…”
Section: Discussionmentioning
confidence: 99%